2007
DOI: 10.2522/ptj.20060178
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Changes in the Trapezius Muscle and Overlying Skin Following Transcutaneous Electrical Nerve Stimulation

Abstract: Muscle contractions induced by motor-level 2-Hz TENS appear to be a prerequisite for increasing blood flow in the trapezius muscle. However, high stimulation intensity may prevent increased blood flow in the overlying skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
3
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 20 publications
5
76
3
7
Order By: Relevance
“…In these studies, the stimuli were applied to the postganglionic neurons. On the other hand, the low frequency TENS, which acts more on the motor threshold (Chesterton et al, 2003) and when applied to the portion of a distal segment (postganglionic neuron) improved muscle contraction and increased peripheral vascular resistance (Miller et al, 2000;Sandberg et al, 2007), resulting in an increase of the cardiac sympathetic activity immediately after application, as demonstrated in this present study. However, this low frequency stimulation when applied to the preganglionic region reduces cardiac sympathetic activity (Sherry et al, 2001), since it does not generate contraction of the muscle of the distal segments and consequent increase of peripheral vascular resistance.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In these studies, the stimuli were applied to the postganglionic neurons. On the other hand, the low frequency TENS, which acts more on the motor threshold (Chesterton et al, 2003) and when applied to the portion of a distal segment (postganglionic neuron) improved muscle contraction and increased peripheral vascular resistance (Miller et al, 2000;Sandberg et al, 2007), resulting in an increase of the cardiac sympathetic activity immediately after application, as demonstrated in this present study. However, this low frequency stimulation when applied to the preganglionic region reduces cardiac sympathetic activity (Sherry et al, 2001), since it does not generate contraction of the muscle of the distal segments and consequent increase of peripheral vascular resistance.…”
Section: Discussionsupporting
confidence: 68%
“…In this context, TENS is presented as a potential therapeutic resource able to interact in different clinical conditions, such as hypertension, in addition to its analgesic effects widely described in literature (Chesterton et al, 2002;Sbruzzi et al, 2012;Vance et al, 2014;Bi et al, 2015). This interaction of TENS with the cardiovascular system is demonstrated by vasodilation (Cramp et al, 2000;Miller, Gruben, & Morgan, 2000;Sherry et al, 2001;Vieira et al, 2012), increased blood in peripheral and coronary blood flow (Chauhan et al, 1994;Jessurun et al, 1998;Cramp et al, 2000;Miller et al, 2000;Sandberg, Sandberg, & Dahl, 2007), decreased peripheral vascular resistance (Mannheimer, Emanuelsson, & Waagstein, 1990;Sherry et al, 2001), and heart rate (Nitz, 2003). The combination of these mechanisms reduces the blood pressure demonstrated in healthy volunteers (Sherry et al, 2001;Nitz, 2003;Vieira et al, 2012) and in hypertensive patients (Kaada et al, 1991;Jacobsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation may vary depending on the duration, intensity, and area of application 16 . Previous studies have demonstrated that time of electrical stimulation seem to promote different responses, changes in local circulation 10,[17][18][19] , increase in myocardial oxygen, and reduction in oxygen demand 20 ; however, it is still unclear whether interferential current stimulation can improve blood flow during muscle metaboreflex induction. Indergand and Morgan 10 applied IES for only 10 min 10 , but in our study, the opposite results were obtained when IES was applied for 30 min, suggesting that improvement of blood-flow control might be time-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that a similar effect occurred also with magnetic stimulation. Recently, there has been an increasing number of reports on deep venous thrombosis prophylaxis by increasing venous return via electrical stimulation of the peripheral nerves (4,6,19,26). Since high-frequency peripheral nerve magnetic stimulation can be performed without direct contact, it is applicable for patients immobilized with a cast.…”
Section: Changes In Peripheral Venous Blood Flow Due To Repetitive Mamentioning
confidence: 99%